PENGARUH KINERJA KEUANGAN DAN STRUKTUR KEPEMILIKAN terhadap Pengungkapan Laporan Keuangan Perusahaan Jasa - Sari, Dinda Permata; Andayani, Andayani (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
One of the changes of the economic environment has influence in the business world. In order to be more competitive, companies are confronted in the condition to be more transparent in disclosing the information of their company. The financial analysis ratio is an alternative to examine whether this financial information is benefit to conduct classification to the profit in the future. The purpose of this research is to test the influence of financial performance variable with the calculation of return on asset, and the ownership structure to the disclosure of the financial statement on the service companies which are listed in Indonesia Stock Exchange in 2011-2013 periods. The samples are 15 service companies which are listed in Indonesia Stock Exchange and these companies have been selected by using purposive sampling. Multiple linear regressions and hypothesis test which has been done by using the f- statistics. Moreover, classic assumption test which includes normality test, multicolinearity test, heteroscedasticity test, and autocorrelation have been conducted in this research. The result of the research shows that return on asset variable has positive and significant influence to the disclosure of financial statement; managerial ownership structure has positive and insignificant influence to the financial statement; domestic institution ownership structure has positive and insignificant influence to the disclosure of financial statement; foreign institution ownership structure has positive and significant to the disclosure of financial statement; the public ownership structure has positive and insignificant influence to the disclosure of the financial statement.Keywords: Financial Performance, Ownership Structural and the Disclosure of Financial Statement.